Inclusion of students with special educational needs: the case of a portuguese public university - Santos, Evelyn (2018)
Attention to the inclusion of students with special educational needs (SEN) has been an increasingly reality in education. New practices in favor of physical, attitudinal and digital accessibility for students have also been perceived in Higher Education. In the case of Portugal, a greater number of students with SEN are enrolled in Higher Education Institutions (HEI). Among many reasons, it is believed that the support of a policy presenting a Special Access Contingent that guarantees a number of places for students with SEN, can be one of the main aspects. However, at national level, policies for inclusion in higher education that guarantee the rights and permanence of students with SEN are not verified. Given this reality, HEI have created internal statutes and supported the students on a case-by-case basis. On the one hand, these support initiatives can favor the trajectory of the students, on the other, they place the student to be at the mercy of the sensibility of HEIs. In this sense, this study presents, in a qualitative context, the perceptions of 10 students with different SEN, of several cycles and courses on inclusion in a Portuguese Public University. We aim to represent the main supports offered by the HEI, evidenced by the students, as enhancers of inclusion in Higher Education. The data were collected by semi-structured interviews and analyzed using the content analysis technique with the support of the qualitative analysis software webQDA. From the results, it was verified that the students reported being satisfied with the different the different supports offered by the HEI. From these results, we differentiated three categories of accessibility, being presented in order of greater reference: 1. attitudinal (187 references), 2.physical/structural (49 references) and 3.digital/material (48 references). It is noticeable that all these aspects merge, and a work of cohesion between all the supports listed is necessary. In this sense, the present work aims to promote reflection on the dimensions of support for the inclusion of students with SEN in Higher Education, based on the reality of a Portuguese public HEI.